设A,B为任意两个随机事件,且P(A)>0,则[img=144x25]18035d89f2d8eba.png[/img]
A: P(AB)
B: P(A)
C: P(B)
D: 1
A: P(AB)
B: P(A)
C: P(B)
D: 1
D
举一反三
- 设A,B为两个随机事件,且P(AB)>0,则[img=101x25]1802e2a9e486bd1.png[/img]( ) A: P(B) B: P(AB) C: [img=73x25]1802e2a9ecee1f0.png[/img] D: 1
- 设A,B为两个随机事件,且P(AB)>0,则P(AB)>0,则P(A|AB)=()。 A: P(B) B: P(AB) C: P(A∪B) D: 1
- 设A,B为两个随机事件,且P(AB)>0,则P(A|AB)=() A: 1 B: P(A) C: P(A|B) D: P(AB)
- 设A,B为两个随机事件,且P(AB)>0,则P(A|AB)=() A: P(A) B: P(AB) C: P(AIB) D: 1
- 设A,B为两个随机事件,且P(AB)>;0,则[img=101x25]17de92757761bb6.png[/img]( ) 未知类型:{'options': ['P(B)', 'P(AB)', '', '1'], 'type': 102}
内容
- 0
设A与B为两个随机事件,且P(AB)>0,则P(A|AB)=( ). A: P(A) B: P(AB) C: P(A|B) D: 1
- 1
设A和B为两个随机事件,且P(AB)>0,则P(A|AB)= A: P(B) B: P(AB) C: P(AB) D: 1
- 2
设A,B为两个随机事件,且P(A)>0,则P(A∪B|A)=() A: P(AB) B: P(A) C: P(B) D: 1
- 3
设A,B为两个随机事件,且P(A) > 0,则P((A∪B)|A) = A: P(AB) B: P(A) C: P(B) D: 1
- 4
设A,B为两个随机事件,且P(A)>0,则P(A∪B|A)=() A: P(AB) B: P(A) C: P(B) D: 1